Age of bronze (1998), volume 3a ebook Betrayal pt 1. - Shanower, Eric (Age of Bronze (1998), 2018)
High King Agamemnon lusts to conquer the wealthy city of Troy. He leads his army across the sea, fighting all the way. On the island of Tenedos, just off the coast of Troy, Achilles leads the attack. Spears fly and men die. When the dust settles, Achilles finds himself one step closer to his tragic fate. Meanwhile, the Trojans prepare their defenses and gather allies. Agamemnon's offer of a peace embassy to King Priam reassures few. War appears inevitable. Even Helen dreads to face what lies ahead for her and everyone she loves or once loved. Collects AGE OF BRONZE #20-26 the award-winning (Eisners 2001 and 2003, Gran Guinigi 2006) retelling of the Trojan War.. Author: Eric Shanower. Illustrator: Eric Shanower . 2007 Eric Shanower.